Seismic performance evaluation of assembled GCFST column-section steel beam frames with geopolymer concrete walls. (December 2020) - Zhou, Zhongyi; Wang, Tao; Hui, Cun; Li, Jianhua
Abstract: A new type of assembled lightweight geopolymer concrete filled steel tube (GCFST) columns frame with controllable deformation connected geopolymer concrete walls (GCW) structure has been proposed in this paper. In order to study the seismic performance of the proposed frame, three full size assembled lightweight GCFST column-section steel beam frame with GCW specimens with different connection forms (GSTFW-2, GSTFW-3 and GSTFW-4) were designed based on an assembled lightweight GCFST column-section steel beam frame specimen with number GSTFW-1. The GSTFW-2 is an assembled lightweight frame with strongly connected geopolymer concrete wall. The GSTFW-3 is an assembled lightweight frame with all around controllable deformation connected geopolymer concrete wall. The GSTFW-4 is an assembled lightweight frame-geopolymer concrete wall with upper and bottom controllable deformation connection. Low-cycle reversed loading experiments of the four specimens are carried out. Based on the experiments, the damage process and failure modes of each specimen are analyzed. The load-bearing capacity, displacement, hysteretic performance, energy dissipation and ductility of each specimen were studied. The results show that the proposed controllable deformation connection has great impact on the seismic performance of the proposed frame. The assembly parts of the assembled lightweight frame are connected reliably with good integrity of the frame, strong elastic-plastic deformation capacity, high energy dissipation capacity and good aseismic performance. The assembly parts have light weight and the construction is simple. It is convenient for popularization and application in rural areas with low degree of mechanization.